Have We Vindicated the Motivational Unconscious Yet? A Conceptual Review - Billon, Alexandre (Frontiers in Psychology, 2011)
Motivationally unconscious (M-unconscious) states are unconscious states that can directly motivate a subject’s behavior and whose unconscious character typically results from a form of repression. The basic argument for M-unconscious states claims that they provide the best explanation to some seemingly non rational behaviors, like akrasia, impulsivity or apparent self-deception. This basic argument has been challenged on theoretical, empirical and conceptual grounds. Drawing on recent works on apparent self-deception and on the ‘cognitive unconscious’ I assess those objections. I argue that (i) even if there is a good theoretical argument for its existence, (ii) most empirical vindications of the M-unconscious miss their target. (iii) As for the conceptual objections, they compel us to modify the classical picture of the M-unconscious. I conclude that M-unconscious states and processes must be affective states and processes that the subject really feels and experiences —and which are in this sense conscious— even though they are not, or not well, cognitively accessible to him. Dual process psychology and the literature on cold-hot empathy gaps partly support the existence of such M-unconscious states.